2017
DOI: 10.1098/rsos.171570
|View full text |Cite
|
Sign up to set email alerts
|

Deepest and hottest hydrothermal activity in the Okinawa Trough: the Yokosuka site at Yaeyama Knoll

Abstract: Since the initial discovery of hydrothermal vents in 1977, these ‘extreme’ chemosynthetic systems have been a focus of interdisciplinary research. The Okinawa Trough (OT), located in the semi-enclosed East China Sea between the Eurasian continent and the Ryukyu arc, hosts more than 20 known vent sites but all within a relatively narrow depth range (600–1880 m). Depth is a significant factor in determining fluid temperature and chemistry, as well as biological composition. However, due to the narrow depth range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 84 publications
(143 reference statements)
1
32
2
Order By: Relevance
“…subglabra was formed earlier than that for P. clathrata during the geological history of the Okinawa Trough. Provanna clathrata appears to have adapted to deeper depths and only occurs below 1400 m deep, whereas P. subglabra appears to occur throughout a wide depth range ( Table 1 ; also see Miyazaki et al, 2017 ). This agrees with the fact that depth of the back-arc basin spreading centre increases with time, meaning the deeper sites suitable for P. clathrata came into existence later than the shallower sites suitable for P. subglabra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…subglabra was formed earlier than that for P. clathrata during the geological history of the Okinawa Trough. Provanna clathrata appears to have adapted to deeper depths and only occurs below 1400 m deep, whereas P. subglabra appears to occur throughout a wide depth range ( Table 1 ; also see Miyazaki et al, 2017 ). This agrees with the fact that depth of the back-arc basin spreading centre increases with time, meaning the deeper sites suitable for P. clathrata came into existence later than the shallower sites suitable for P. subglabra.…”
Section: Discussionmentioning
confidence: 99%
“…The northwestern Pacific is an excellent model system for examining such evolutionary processes, since there are back-arc vents (e.g., Okinawa Trough, Manus Basin) and hydrocarbon seeps (e.g., Sagami Bay, Nankai Trough) in close proximity. The Okinawa Trough is a back-arc basin with more than 10 known hydrothermal vent fields, and more continue to be discovered ( Ishibashi et al, 2015 ; Nakamura et al, 2015 ; Chen et al, 2017 ; Miyazaki et al, 2017 ). As these vents appeared only two million years ago at the southern end of the back-arc basin, the historical evidence of animals invading these habitats can still be recovered genetically, along with ongoing evolutionary and ecological processes.…”
Section: Introductionmentioning
confidence: 99%
“…MeSH can be produced from the methylation of H 2 S (Drotar et al, 1987) or degradation of Met and S-methylcysteine (Bremner and Steele, 1978;Ferchichi et al, 1985;Taylor and Kiene, 1989). Okinawa Trough hydrothermal vents have been reported to be rich in H 2 S (Miyazaki et al, 2017a), additionally, Kawagucci et al (2013) found that H 2 S content reached 4.5 mM kg −1 in hydrothermal sediments in the northern Iheya. Therefore, we propose that much of the MeSH in the Okinawa hydrothermal field is likely to be produced from H 2 S methylation.…”
Section: The Okinawa Trough Hydrothermal Field Has Its Own Specific Dmentioning
confidence: 99%
“…However, given that a variety of mud volcanoes, pockmarks, and cold seeps have been discovered in recent decades in the OT (Yin et al, 2003;Li et al, 2015;Sun et al, 2015;Xu et al, 2018), it is reasonable to infer that they may contribute a substantial amount of CH 4 to seawater. In addition, as a universal extreme system within the OT, modern hydrothermal activity is pervasive and vigorous from north to south, which can also discharge a large amount of CH 4 along with hydrothermal fluids (Sakai et al, 1990;Ishibashi et al, 1995Ishibashi et al, , 2014Inagaki et al, 2006;Miyazaki et al, 2017). Previous studies found that the distance between the site of the newly discovered cold seeps (Li et al, 2015;Xu et al, 2018) and the hydrothermal vents found in the past (Inagaki et al, 2006;Ishibashi et al, 2014) are less than several tens of kilometers apart.…”
Section: Introductionmentioning
confidence: 99%